Permeant ion binding affinity in subconductance states of an L-type Ca(2+) channel expressed in Xenopus laevis oocytes - Cloues, Robin K (Blackwell Science Inc, 2000)
1. The relationship between single-channel conductance and ion binding affinity in Ca(2+) channels was investigated by measuring differences in the apparent binding affinity (K′(D)) for Ca(2+) among naturally occurring conductance states of an L-type (α(1C)) Ca(2+) channel heterologously expressed in Xenopus oocytes. Using cell-attached patch recordings, three or more conductance levels were observed when Ca(2+), Ba(2+) or Li(+) was used as the permeating ion. 2. With Li(+) as the charge carrier, low concentrations of Ca(2+) (0.1–3.0 μM) produced discrete blocking events in all conductance states. Measurements of open and blocked times as a function of Ca(2+) concentration were used to calculate rates of block and unblock. 3. K′(D) was calculated for three of the conductance levels. Binding affinity for Ca(2+) increased as conductance decreased (K′(D): large = 7.5 μM, medium = 4.0 μM, small = 2.7 μM). The lower K′(D) values of the smaller conductance states arose from a combination of larger on-rates and smaller off-rates. 4. These results imply that permeant ions such as Ca(2+) have both easier access to, and longer dwell time in, the Ca(2+) binding locus in the pore when the channel opens to a subconductance level as compared to the fully open level. 5. The difference in K'(D) between the large and small conductance levels corresponds to a small difference in the free energy of binding, ΔΔG≈ 1k(B)T, where k(B) is Boltzmann's constant and T is absolute temperature (kelvin). Nonetheless, an Eyring model of Ca(2+) channel permeation incorporating the state-specific on- and off-rate constants for Ca(2+) was able to reproduce the large difference in channel conductance, indicating that small differences in binding energy may be able to account for large differences in amplitude between conductance states.